A Quality and Reliability Analysis of Geriatric Exercise Videos on YouTube - Burcu Ortanca; Gizem Sarıçimen; Fulya Bakılan; Onur Armağan; Cengiz Bal (Galenos Yayinevi, 2024)
Objective: The aims were to (1) analyze the exercise content of the most viewed videos among the exercise videos published in English for geriatric individuals on YouTube and (2) examine the videos in terms of reliability and quality. Materials and Methods: A YouTube search was performed in January 2023, and 150 videos were included. Video metrics: number of views, likes, dislikes, comments, video duration, and exercise types were evaluated. The popularity, reliability, and quality of videos were evaluated using the Video Power index, modified DISCERN score, and global quality score (GQS), respectively. Results: Most of the exercise videos were about strengthening and stretching. According to the GQS, 25.3% of the videos were of low quality, 52.7% were of moderate quality, and 22% were of high quality. Most of the information providers were medical doctors in the high-quality group (p<0.001), DISCERN scores (low moderate quality: p<0.001, low high quality: p<0.001) were different according to quality level. Video duration and number of comments were lower in the high-quality group (p=0.003). Conclusion: Videos with short duration and few comments, regardless of the number of likes or dislikes, can also be high-quality videos. To make an appropriate choice of exercise videos on YouTube, geriatric individuals should select videos uploaded by medical doctors and official institutions.